2009
DOI: 10.1080/01496390902886013
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring ZnS Precipitation: Estimation, Error Analysis and Experiment Design

Abstract: A mass balance model of total soluble sulfide and free zinc with a second-order reaction term is theoretically able to reconstruct the zinc effluent concentration and the kinetic parameter (k). However, under real conditions this model predicts the zinc effluent concentration four orders of magnitude higher than the measured ones. The applied error analysis, based on linearization of the model followed by first-order variance propagation, showed that the accuracy of several of the input variables (flows and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…This difference between the concentration of zinc and total sulfur could be due to the presence of byproducts in the ZnS or formation of other products during the solubilization process. It was mentioned by [23] that a soluble species Zn(HS)n could be present in the aqueous solution. They also observed an excess of total sulfur even though sulfur was added in stoichiometric quantities [23].…”
Section: Presence Of Colloidal Particles Might Contribute To the Solumentioning
confidence: 99%
See 1 more Smart Citation
“…This difference between the concentration of zinc and total sulfur could be due to the presence of byproducts in the ZnS or formation of other products during the solubilization process. It was mentioned by [23] that a soluble species Zn(HS)n could be present in the aqueous solution. They also observed an excess of total sulfur even though sulfur was added in stoichiometric quantities [23].…”
Section: Presence Of Colloidal Particles Might Contribute To the Solumentioning
confidence: 99%
“…It was mentioned by [23] that a soluble species Zn(HS)n could be present in the aqueous solution. They also observed an excess of total sulfur even though sulfur was added in stoichiometric quantities [23]. The formation of complexes has been discussed by several authors; nonetheless the existence of those complexes cannot be easily proved [4,5,8,24].…”
Section: Presence Of Colloidal Particles Might Contribute To the Solumentioning
confidence: 99%
“…However, from other experimental data with much lower zinc concentrations, around 10 −5 g/l, less satisfactory results have been found. Further analysis of this phenomenon indicated that the accuracy of the measurements of flows and concentrations plays a crucial role in the estimation of the zinc concentration and reaction constant [16].…”
Section: Discussionmentioning
confidence: 99%